GAMBARAN HASIL PEMERIKSAAN KOH DARI KEROKAN KULIT KAKI PADA PEMULUNG DENGAN TINEA PEDIS DI KOTA MEDAN - JOICE SONYA GANI PANJAITAN; SUHARTOMI SUHARTOMI (JURNAL ILMIAH KOHESI, 2023)
KOH examination of skin scrapings can reveal a variety of microbiological features. Therefore, this study aims to analyze the results of the KOH examination of scavengers who have tinea pedis in Medan City. This research is a cross sectional study of 60 scavengers in Medan City selected by purposive sampling. The results of this study indicate that the majority of scavengers who experience tinea pedis in Medan City are in the Medan Denai area (70%). In addition, the majority of scavengers who experience tinea pedis are women who tend to be 48 years old with a low level of education ranging from uneducated to elementary school (48.3%). From the results of KOH examination of 10% of the skin scrapings, it was found that the most hyphae (80%) and the least were a combination of hyphae and spores (8.3%). Therefore, it can be concluded that the most common KOH examination feature found from skin scrapings of tinea pedis patients is fungal hyphae.